Microvascular Dynamics and Hemodialysis Response of Patients With End-Stage Renal Disease - Lee, Jen-Shih; Lee, Lian-Pin (Frontiers in Bioengineering and Biotechnology, 2022)
As ESRD patients undertake a 4-hour long hemodialysis, ultrafiltrate with a volume equivalent to 80% to 100% of the total plasma volume is extracted by the dialyzer. In not making the patient to become highly hypovolemia, a large volume of interstitial fluid must be restituted through the endothelia lining of the microcirculation to refill the circulation. The microcirculation and the spleen can also shift some of its blood volume to improve cardiac filling. In this paper, we will first review the morphometric and hemodynamic characteristics of the microcirculation and the spleen that are important to fluid restitution, microvascular volume shift and splenic erythrocyte release. The fluid and protein movement across the endothelia lining of microvessels are characterized by filtration coefficient, permeability fraction and reflection coefficient. A full circulation analysis is employed to reveal why a larger filtration coefficient, a larger permeability fraction and/or a larger reflection coefficient can cause a lesser increment in the plasma protein concentration, a lesser increase in plasma colloidal osmotic pressure, a lesser reduction in microvascular blood pressure, more fluid restitution from the tissue and a lesser reduction in plasma volume. The hemodynamics of the splenic microcirculation is examined to suggest that the splenic RBC release may not lead to an increase in blood volume. Finally a way is presented to estimate the likely change in microvascular blood pressure, the microvascular blood volume reduction, and then the filling of the venous macrocirculation. A better understanding of how the factors examined here cause hypovolemia can be the basis for one to modify the hemodialysis process such that the development of hypovolemia can be avoided over the course of hemodialysis.